Reflective Practice: Adult Student Engagement in Character Education - Samuel Beaumont (Journal of Scholarly Engagement)
This paper outlines how I assessed and revised a proprietary character education program of study administered to non-traditional students attending an accelerated academic program at a Hispanic-Serving Institution. John Dewey’s reflection practice doctrine provided the theoretical foundation and lens for conducting the analysis. Given the unique characteristics associated with non-traditional students, three main challenges are outlined: (1) students matriculate at varying levels of academic readiness and moral development, (2) there is low student engagement rate in character education, and (3) there is limited time for ethical instruction in a full academic curriculum and busy student lives. The reflection process included quantitative data from the Defining Issues Test-2 and qualitative data from observations, student and staff responses, and interviews. The presentation concludes with key takeaways and recommendations for future research.